The International Geomagnetic Reference Field in Yemen at the Beginning of 2020 and The Secular Variations during the Period from 1900 to 2020 - Al-Akhaly, Ibrahim A. Al-Akhaly (Journal of Pure & Applied Sciences, 2021)
The International Geomagnetic Reference Field (IGRF) is the best mathematical fit of the observed geomagnetic field at any specific time. It is adopted by the International Association of Geomagnetism and Aeronomy (IAGA). Due to the importance of this field for navigation, magnetic survey, geological mapping, military usage, local magnetic anomalies in the Earth's crust, surveying, and orientation in three dimensions. The IAGA evaluates and updates this field every five years to account for temporal field variations originating in Earth's core. The elements of the IGRF were determined for 1970 and the beginning of 2020 for the 171 sites in Yemen to compare and determine secular variations during this period. Also, the IGRF elements were determined for the centers of three cities; Aden, Sana’a and Sa'dah at the beginning of every five years from 1900 to the beginning of 2020 to study the secular variation during this period.